Palaeomagnetic Studies in the British Caledonides--II The Younger Gabbros of Aberdeenshire, Scotland - Sallomy, J. T.; Piper, J. D. A. (Geophysical Journal International, 1973)
A palaeomagnetic survey of the Younger Gabbros of north—east Scotland is presented. Forty-one sites have been sampled from seven gabbro masses (Belhelvie, Arnage, Maud, Insch, Huntly, Boganclogh and Haddo House) of which the NRM at 37 of these sites is significantly grouped. The bulk of the collection shows high stability on AF and thermal cleaning and 32 sites have significant direction after cleaning and yield a stable direction D = 168°, I = + 34° ( k = 9.7). All sites have the same polarity. A palaeomagnetic north pole is derived at 9° E, 11° S which is 16° away from a previous estimate for the gabbros based on total NRM only. A fold test has been applied to the igneous lamination of three of the bodies and it is concluded that the bodies were subjected to local F 3 folding above their Curie point which, in most of the samples tested, falls in the range 500–600° C. The Rb-Sr and K-Ar data for the gabbros are reviewed and the best estimate of the magnetic age is approximately 470 My.